Ramalan berstokastik terhadap potensi takaful wakaf dalam meningkatkan dana wakaf tunai - Zaidi Isa,; Rubayah Yakob,; Nurul Hidayah Md. Razali,; Mohd Hafizuddin Syah Bangaan Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Takaful waqf is one of the collection methods to increase the amount of cash waqf in Malaysia. Meanwhile, a takaful plan is an economic mechanism that has been proven to minimize the financial risk of takaful participants. However, the ability of the takaful plan to increase the waqf collection through takaful waqf remains questionable. Therefore, this study aims to predict the potential of takaful waqf objectively and calculate the probability of the potential accessibility of takaful waqf plans in increasing the collection of cash waqf funds. This study uses secondary data obtained from the Department of Statistics Malaysia, Syarikat Takful Ikhlas, Malaysian Takaful Association and Bank Negara Malaysia. The potential of takaful waqf is calculated based on several models with certain assumptions using stochastic values through the Monte Carlo Simulation Method. This study proves that takaful operators can employ two models to increase cash waqf collection through takaful waqf. The first model assumes waqf collection is subject to the death of a motor takaful participant. If the entire motor takaful operators participate, the potential collection could reach up to RM1 million. At 90% accessibility, this model predicts a cash waqf collection of RM907,000. Meanwhile, the second model which presumes that waqf benefits are obtained from a 1-3% deduction from the takaful contribution of each participant and enrollment from all motor takaful operators provides much better potential. This model estimates cash waqf collection up to RM83 million and at 90% accessibility this model predicts cash waqf collection of RM41 million. The results of this study could assist the waqf and takaful authorities in formulating more objective strategic plans to ensure the sustainability and continuity of the takaful waqf plan